The Importance of Transformational Leadership and Its Influence on Crew Performance on Ships - Supangat, Supangat; Marsudi, Sugeng (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
This study explores how transformational leadership influences crew motivation, collaboration, and productivity in the unique and often challenging work environment at sea. The study used a qualitative approach by collecting data through in-depth interviews with crews from various types and sizes of vessels. Data analysis was conducted to identify patterns and themes related to the influence of transformational leadership on crew attitudes and behaviors. The results showed that transformational leadership, which includes an inspiring vision, motivation, intellectual stimulation, and individual attention, positively influences crew performance. Leadership that is able to inspire and empower crews not only improves compliance with safety and operational procedures, but also strengthens team bonds and increases adaptability to challenges faced at sea.